Management of Moderate and Severe Forms of Psoriasis in Children: New Opportunities of Genetically Engineered Biologic Drugs - Leyla S. Namazova-Baranova; Andrey L. Bakulev; Nikolay N. Murachkin; Lyudmila N. Nam; Roman A. Ivanov ("Paediatrician" Publishers LLC, 2021)
The article shows the key role of IL-17 in the psoriasis pathogenesis and the opportunities of its management via monoclonal antibodies product secukinumab. The review of international randomized trials on clinical efficacy and safety of genetically engineered biologic drug secukinumab in children and adolescents with psoriasis is presented. During treatment periods of 12 to 52 weeks, secukinumab has shown high therapeutic efficacy for psoriasis severity and skin lesion areas and has improved quality of life of children and adolescents according to dynamic assessments of PASI, IGA 0/1 mod 2011 indices, CDLQI questionnaire. The safety profile of secukinumab in children is estimated as favorable and comparable to using it in adults.